ORGANIZATIONAL CITIZENSHIP BEHAVIOR, KEPEMIMPINAN TRANSAKSIONAL, DAN KOMITMEN ORGANISASIONAL: PENGARUHNYA TERHADAP KINERJA KARYAWAN - Archita Kumala Devi, Ni Putu Ayu; Sintaasih, Desak Ketut (E-Jurnal Manajemen, 2016)
The development of tourism in Badung as pillars being the power of the Balinese economy should put human resources that are reliable and have good performance as human capital. The purpose of this study was to determine the effect of organizational citizenship behavior (OCB), transactional leadership and organizational commitment to employee performance. This research was conducted in Kamuela Villa Seminyak engaged in the tourism business. Sample of 60 people with a sampling technique using census method. Data were analyzed using multiple linear regression analysis. The survey results revealed that organizational citizenship behavior, transactional leadership and organizational commitment partially positive and significant influence on employee performance. And organizational commitment variable as the variable most dominant influence. To improve the performance of employees, company leaders should provide a working understanding of the way it clear to employees that the effective implementation of the work so that the work can be completed quickly
Keywords: organizational citizenship behavior, transactional leadership, organizational commitment and perfomance